Case report on Caffeys disease in an adolescent with a familial aspect - Kanjalkar, Milind; Jethwa, Prachi; Adaniya, Atul (Indian Journal of Child Health, 2024)
Caffey’s disease is a bone disorder that most often occurs in babies. It is inherited in an autosomal dominant pattern but not all people who inherit the genetic change develop signs and symptoms. Most people with Caffey’s disease have no further problems related to the disorder after early childhood. Occasionally, another episode of hyperostosis occurs years later. The peculiarity about this case was its presence in the adolescent stage of the child’s growth. This condition is mostly underreported due to its regression in childhood itself, and hence we have reported this unique case. The parents presented with complaints of a different etiology and with complaints of bone pains and deformity since birth. He was diagnosed primarily with Caffey’s disease after ruling out other diagnoses. There is very little literature on Caffey’s disease due to its regression in early childhood.